Optimal training frequency for acquisition and retention of high-quality CPR skills: A randomized trial - Anderson, Robert; Sebaldt, Alexandre; Lin, Yiqun; Cheng, Adam (Resuscitation, 2019)
Spaced training programs employ short, frequent CPR training sessions to improve provider skills. The optimum training frequency for CPR skill acquisition and retention has not been determined. We aimed to determine the training interval associated with the highest quality CPR performance at one year. Participants were randomized to 1-month, 3-month, 6-month, and 12-month CPR training intervals over the course of a 12-month study period. Practice sessions included repeated two-minute CPR practice sessions with visual feedback and verbal coaching until Excellent CPR was achieved, to a maximum of three attempts. Excellent CPR was defined as a two-minute CPR session with ≥90% of compressions with a depth of 50–60 millimeters, a rate of 100–120 per minute, and with complete chest recoil. CPR performance was assessed in all groups at 12 months. The primary outcome was the proportion of participants able to perform Excellent CPR in each group. A total of 167 participants were included in the analysis. Baseline assessment showed no difference in CPR performance (p = 0.38). Participants who were trained monthly had a significantly higher proportion of Excellent CPR performance (58%) than those in all other groups (26% in the 3-month group, p = 0.008; 21% in the 6-month group, p = 0.002; and 15% in the 12-month group, p < 0.001). Short-duration, distributed CPR training on a manikin with real-time visual feedback is effective in improving CPR performance, with monthly training more effective than training every 3, 6, or 12 months.